Proyecto de Inversión para la Creación de una Empresa Productora de Panela en el Cantón Quilanga de la Provincia de Loja - Valarezo Chávez, Celia María (2017)
With the purpose of helping the socio-economic development of the Canton Quilanga and support to small farmers who cultivate sugar cane, raises the present draft which is called "INVESTMENT PROJECT FOR THE CREATION OF A COMPANY PRODUCING PANELA IN THE CANTON QUILANGA OF LOJA province", with the main objective to determine the feasibility of the project. To comply with the overall objective was necessary the approach of specific objectives as are: Carry out a market study to assess the feasibility of the project, perform the technical study which will establish the location, size, capacity and the engineering of the project, designing the organizational study and legal that best fits to the constitution of the company and carry out the study financial and economic evaluation in order to determine the feasibility of the investment project. For the foundation of the Thesis, was used some methods and research techniques; among which we have scientific method, deductive, inductive, analytical and synthetic, and the techniques used were the survey, direct observation and collection bibliography. To comply with the first specific objective is conducted surveys directed to families of the city of Loja place where you are going to distribute the panela in cubes by determining the sample of 381, was obtained with information relevant to the conduct of the study of market where it detected the existence of unsatisfied demand for the 6 justification and implementation of the project, and met the most commonly used means of communication by families designing the respective market plan to publicize the product. In the technical study was established the size of the company according to the unsatisfied demand existing on the market, concluding that used the 82 per cent of the installed capacity and each year will increase 2 per cent until the last year to cover with 100%, the adequate location of the Company was established using the method of qualitative points determining that will be located in the Canton Quilanga of Loja province in the neighborhood of San Pedro to a 1 kilometer of track Amaluza; in terms of the engineering of the project it was established that the production process will be semi-industrial, has designed the distribution of the plant with the requirements that the company needs. Legal study and organizational makes reference to the legal constitution of the company, which is a limited company and is supported by three founding partners, developed features manual, manual of industrial security and the organizational structure of the company, detailed legal rules and requirements for the full functioning. For the determination of the financial study were made quotations in the market, to determine actual values of the prices of each instrument necessary for operation of the company andperforming calculations. 7 It was determined the value of the initial investment, capital of work that requires monthly to cope with the obligations acquired with suppliers, employees and public institutions, was the projection of costs and expenses, the income structure to determine the selling price and the profit and loss statement. The financial evaluation demonstrated the profitability and viability obtaining positive data that justify the implementation of the project, it is necessary to emphasize that all calculations were projected with the rate of inflation for the ten years of the useful life of the same. Conducting an analysis in detail shows that the project is feasible because in their four studies or stages are you get positive data, it should be emphasized that the profits generated are not as ambitious but it is necessary to encourage the execution of this type of project to take advantage of in some part of the large agricultural production which exists in the canton Quilanga and in the province of Loja in general to assist the economic development of the place of impact of the project